The connection between international student mobility and employability : a descriptive study among Finnish employers - Hyvärinen, Ida (2019)
International study and training experiences are commonly thought to increase graduate employability. However, only a few studies have attempted to investigate how international experiences are viewed by employers. The purpose of the present study is to explore the perceptions of Finnish employers by focusing on the following questions: 1) What are the competences valued by employers when recruiting graduates? 2) How do employers perceive international competences? 3) What is the role of international experience in recruitment decisions?